Quantification of drudgery and ergonomics assessment of weeding activity in vegetable production system - Burman, R R; Joshi, Pratibha; Sharma, J P; Sharma, Nishi; Mahra, Girijesh Singh; Sharma, Shailendra; Kumar, Rajesh; Singh, Rahul; Chahal, V P; Singh, A K (The Indian Journal of Agricultural Sciences, 2020)
Weeding activity in vegetable cultivation carried out by women is one of the drudgery prone activities. Women are regularly adopting poor and static posture while doing weeding for long hours by traditional equipment, resulting in various physical load on spine or lumbo-sacral region leads to drudgery coupled with work related musculoskeletal disorders (MSDs). The research paper aims to assess and quantify the drudgery with weeding activity by rural women in which physiological ergonomics evaluation was done for traditional method and with improved technological support with three replications of fifteen minutes work cycle without rest pause. Ergonomic parameters namely Heart Rate, Energy Expenditure Rate, Total Cardiac Cost of Work, Physiological Cost of Work, VO2 Max were measured during the experiments. Observations were recorded on farm women worker with normal health, without any major illness, regularly involved in farm operations and were in the age group of 25 to 45 years. Weeding activity of farm women was quantified and a sample of 10 physically fit rural women having permissible limit of physiological parameters were selected for the study. It was found from investigation that there was reduction in human physiological parameters, viz. heart rate, energy expenditure rate, Total Cardiac Cost of Work, Physiological Cost of work, Blood pressure and Oxygen Saturation.